1996
DOI: 10.1016/s0896-6273(00)80048-3
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Barrels in the Somatosensory Cortex of Monoamine Oxidase A–Deficient Mice: Role of a Serotonin Excess during the Critical Period

Abstract: In a transgenic mouse line (Tg8) deficient for the gene encoding monoamine oxidase A (MAOA), we show that the primary somatosensory cortex (S1) lacks the characteristic barrel-like clustering of layer IV neurons, whereas normal pattern formation exists in the thalamus and the trigeminal nuclei. No barrel-like patterns were visible with tenascin or serotonin immunostaining or with labeling of thalamocortical axons. An excess of brain serotonin during the critical period of barrel formation appears to have a cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
330
2
3

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 487 publications
(356 citation statements)
references
References 61 publications
(25 reference statements)
21
330
2
3
Order By: Relevance
“…In the early postnatal period, serotonin immunoreactivity, 5-HT 1B receptors and SERT each assume a transient pattern localized to layer IV thalamocortical axons [9,10,12,18,26,41,74,76,83,99]. Multiple studies have revealed that manipulation of early 5-HT levels results in significant alterations in the layer IV representations of the rat's whiskers [11,15,16,23,117]. These findings all support a modulatory role for 5-HT on the development and patterning of the thalamocortical innervation, which uses glutamate as its transmitter.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In the early postnatal period, serotonin immunoreactivity, 5-HT 1B receptors and SERT each assume a transient pattern localized to layer IV thalamocortical axons [9,10,12,18,26,41,74,76,83,99]. Multiple studies have revealed that manipulation of early 5-HT levels results in significant alterations in the layer IV representations of the rat's whiskers [11,15,16,23,117]. These findings all support a modulatory role for 5-HT on the development and patterning of the thalamocortical innervation, which uses glutamate as its transmitter.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, serotonin has a trophic influence on the morphogenesis of somatosensory cortex (SI) and the development of patterned glutamatergic thalamocortical connections [26,41,74,99]. Alterations in cortical 5-HT levels affect the patterning of thalamocortical maps, such as in rodent barrel field [11,16,23]. Moreover, Djavadian et al [45] report that 5-HT depletion in neonatal cats reduces pruning of callosal axons to visual cortex, resulting in a doubling of labeled projection neurons while maintaining their overall topography.…”
Section: Introductionmentioning
confidence: 99%
“…183 Increased 5-HT causes disorganization in the somatosensory and visual cortices due to disruption in the clustering and segregation of thalamocortical fibers. 184,185 Similarly, mice with a targeted disruption of Sert also have an excess of 5-HT in the extracellular space, leading to disruption of somatosensory cortex formation, reduction of apoptosis in the telencephalon 186,187 and variable alterations in cortical layer thickness and neuronal cell density, dependent on background strain. 188 Sert-null mice also show an altered behavioral phenotype, including hypolocomotion, marked reductions in exploration, and reduced social interaction.…”
Section: Autism Candidate Genes and Synaptic Functionmentioning
confidence: 99%
“…Disruption of the serotonergic system by either pharmacological or genetic manipulations in the neonatal period in rodents results in delayed development of cortical layers, disruption of thalamocortical afferents patterns in the barrel fields, and a decrease or disorganization of the barrel fields (Blue et al, 1991;Bennett-Clarke et al, 1994;Cases et al, 1996;Persico et al, 2001).…”
Section: Introductionmentioning
confidence: 99%